Dynamic Changes of Left Ventricular Performance and Left Atrial Volume Induced by the Mueller Maneuver in Healthy Young Adults and Implications for Obstructive Sleep Apnea, Atrial Fibrillation, and Heart Failure - Orban, Marek; Bruce, Charles J.; Pressman, Gregg S.; Leinveber, Pavel; Romero-Corral, Abel; Korinek, Josef; Konecny, Tomas; Villarraga, Hector R.; Kara, Tomas; Caples, Sean M.; Somers, Virend K. (The American journal of cardiology, 2008)
Using the Mueller maneuver (MM) to simulate obstructive sleep apnea (OSA), our aim was to investigate acute changes in left-sided cardiac morphologic characteristics and function which might develop with apneas occurring during sleep. Strong evidence supports a relation between OSA and both atrial fibrillation and heart failure. However, acute effects of airway obstruction on cardiac structure and function have not been well defined. In addition, it is unclear how OSA might contribute to the development of atrial fibrillation and heart failure. Echocardiography was used in healthy young adults to measure various parameters of cardiac structure and function. Subjects were studied at baseline, during, and immediately after performance of the MM and after a 10-minute recovery. Continuous heart rate, blood pressure, and pulse oximetry measurements were made. During the MM, left atrial (LA) volume index markedly decreased. Left ventricular (LV) end-systolic dimension increased in association with a decrease in LV ejection fraction. On release of the maneuver, there was a compensatory increase in blood flow to the left side of the heart, with stroke volume, ejection fraction, and cardiac output exceeding baseline. After 10 minutes of recovery, all parameters returned to baseline. In conclusion, sudden imposition of severe negative intrathoracic pressure led to an abrupt decrease in LA volume and a decrease in LV systolic performance. These changes reflected an increase in LV afterload. Repeated swings in afterload burden and chamber volumes may have implications for the future development of atrial fibrillation and heart failure.